Economic and environmental aspects attributed to the use of light automotive vehicles tagged in Brazil (Research, Society and Development, 2019)
The present study proposes to evaluate the Brazilian Program of Energy Labeling - PBE / INMETRO, in the scope of light automotive vehicles, in the energy, economic and environmental aspects. Its main purpose is to evaluate the energy benefits in terms of fuel consumption, economic, in terms of reducing annual and environmental costs, reducing greenhouse effect gas emissions, using more efficient vehicles (class A, CONPET Seal), compared to less efficient vehicles (classes B, C, D and E) in Brazil. The article shows an influence of several variables in the average annual total cost of a vehicle in order to highlight a variable with greater impact in choosing a more efficient vehicle.